Hitting the complexity of the TIGIT-CD96-CD112R-CD226 axis for next-generation cancer immunotherapy - Jin, Hyung-Seung; Park, Yoon (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2021)
Antibody-based therapeutics targeting the inhibitory receptors PD-1, PD-L1, or CTLA-4 have shown remarkable clinical progress on several cancers. However, most patients do not benefit from these therapies. Thus, many efforts are being made to identify new immune checkpoint receptor-ligand pathways that are alternative targets for cancer immunotherapies. Nectin and nectin-like molecules are widely expressed on several types of tumor cells and play regulatory roles in T- and NK-cell functions. TIGIT, CD226, CD96 and CD112R on lymphoid cells are a group of immunoglobulin superfamily receptors that interact with Nectin and nectin-like molecules with different affinities. These receptors transmit activating or inhibitory signals upon binding their cognate ligands to the immune cells. The integrated signals formed by their complex interactions contribute to regulating immune-cell functions. Several clinical trials are currently evaluating the efficacy of anti-TIGIT and anti-CD112R blockades for treating patients with solid tumors. However, many questions still need to be answered in order to fully understand the dynamics and functions of these receptor networks. This review addresses the rationale behind targeting TIGIT, CD226, CD96, and CD112R to regulate T- and NK-cell functions and discusses their potential application in cancer immunotherapy.
Keywords: ACTIVATING RECEPTOR CD226; NECTIN-LIKE PROTEINS; NK CELL RECOGNITION; CARCINOMA CELLS; T-CELLS; TIGIT; DNAM-1; ADHESION; CD155; CHECKPOINT